A QUANTITATIVE ANALYSIS OF SUPPLY RESPONSE IN THE NAMIBIAN MUTTON INDUSTRY - Van Wyk, D.N.; Treurnicht, N.F. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Agricultural activities in Namibia contribute 5.5% of Namibia